Baroreflex Modulation During Acute High-Altitude Exposure in Rats - Beltran, Ana Rosa; Arce-Alvarez, Alexis; Ramirez-Campillo, Rodrigo; Vasquez-Munoz, Manuel; von Igel, Magdalena; Ramirez, Marco A.; Del Rio, Rodrigo; Andrade, David C. (My University, 2020)
Baroreflex (BR) control is critically dependent of sympathetic and parasympathetic modulation. It has been documented that during acute hypobaric hypoxia there is a BR control impairment, however, the effect of a natural hypoxic environment on BR function is limited and controversial. Therefore, the aim of this study was to determine the effect of acute High-Altitude exposure on sympathetic/parasympathetic modulation of BR control in normal rats. Male Sprague Dawley rats were randomly allocated into Sea-Level (n= 7) and High-Altitude (n= 5) (3,270 m above sea level) groups. The BR control was studied using phenylephrine (Phe) and sodium nitroprusside (SNP) through sigmoidal analysis. The autonomic control of the heart was estimated using heart rate variability (HRV) analysis in frequency domain. Additionally, to determine the maximum sympathetic and parasympathetic activation of BR, spectral non-stationary method analysis, during Phe (0.05 mu g/mL) and SNP administration (0.10 mu g/mL) were used. Compared to Sea-Level condition, the High-Altitude group displayed parasympathetic withdrawal (high frequency, 0.6-2.4 Hz) and sympathoexcitation (low frequency, 0.04-0.6 Hz). Regarding to BR modulation, rats showed a significant decrease (p< 0.05) of curvature and parasympathetic bradycardic responses to Phe, without significant differences in sympathetic tachycardic responses to SNP after High-Altitude exposure. In addition, the non-stationary analysis of HRV showed a reduction of parasympathetic activation (Phe) in the High-Altitude group. Our results suggest that acute exposure to High-Altitude produces an autonomic and BR control impairment, characterized by parasympathetic withdrawal after 24 h of high-altitude exposure.
Keywords: baroreflex; autonomic nervous system; sympathetic nervous system; parasympathetic nervous system; baroreceptors